Antidermatophytic and Antioxidant Activity of Terminalia arjuna (roxb.) Wight & Arn. Bark - Jha, D.K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTBark of Terminalia arjuna, a well-known medicinal plant, has extensively been used in ayurvedic medicines to treat various diseases. The present study was carried out to evaluate the antidermatophytic and antioxidant activity of the crude extract of bark of Terminalia arjuna. The antagonistic activity of the crude extract was tested against five clinically significant antidermatophytic fungi i.e., Trichophyton mentagrophytes, T. rubrum, T. tonsurans, Microsporum gypseum and M. fulvum using agar cup diffusion method. Acetone, 95 % alcohol and methanol were used as solvents for the extraction of crude from bark. The methanol extract was most effective against T. tonsurans (zone of inhibition 25 mm) and least effective against M. gypseum (zone of inhibition 3 mm). The minimum inhibitory concentration of the crude ranged between 2000 µg/ml to 75 µg/ml. Antioxidant activity was determined using scavenging activity of DPPH (1, 1-diphenyl-2-picrylhydroxyl) radical method. The methanolic bark extracts of 50, 100 and 200 µg/ml concentrations exhibited high free radical scavenging activity respectively. The phytochemical screening showed the presence of alkaloids, tannins, saponins in the extract which could be responsible for the antidermatophytic and antioxidant activities.